2005
DOI: 10.1074/jbc.m407005200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of μ-Opioid Receptors Transfers Control of Gα Subunits to the Regulator of G-protein Signaling RGS9-2

Abstract: In mouse periaqueductal gray matter (PAG) membranes, the -opioid receptor (MOR) coprecipitated the ␣-subunits of the G i/o/z/q/11 proteins, the G␤ 1/2 subunits, and the regulator of G-protein signaling RGS9-2 and its partner protein G␤ 5 . RGS7 and RGS11 present in this neural structure showed no association with MOR. In vivo intracerebroventricular injection of morphine did not alter MOR immunoreactivity, but 30 min and 3 h after administration, the coprecipitation of G␣ subunits with MORs was reduced by up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 56 publications
1
79
0
Order By: Relevance
“…Male albino CD-1 mice (Charles River, Barcelona, Spain) weighing 22-25 g were used, from which PAG membranes enriched in synaptosomes were prepared as described previously (Garzón et al, 2005b). Briefly, 2 mm-thick coronal sections of the PAG from six mice were pooled in ice-cold 25 mM Tris HCl (pH 7.7), 1 mM EGTA, 0.32 M sucrose, protease inhibitor cocktail (Sigma, Madrid, Spain, #P8340), phosphatase inhibitor mixture (Sigma, #P2850) and H89 (Sigma, #B1427).…”
Section: Preparation Of Membranes and The Nuclear Fraction From Mousementioning
confidence: 99%
See 1 more Smart Citation
“…Male albino CD-1 mice (Charles River, Barcelona, Spain) weighing 22-25 g were used, from which PAG membranes enriched in synaptosomes were prepared as described previously (Garzón et al, 2005b). Briefly, 2 mm-thick coronal sections of the PAG from six mice were pooled in ice-cold 25 mM Tris HCl (pH 7.7), 1 mM EGTA, 0.32 M sucrose, protease inhibitor cocktail (Sigma, Madrid, Spain, #P8340), phosphatase inhibitor mixture (Sigma, #P2850) and H89 (Sigma, #B1427).…”
Section: Preparation Of Membranes and The Nuclear Fraction From Mousementioning
confidence: 99%
“…The procedure used to immunoprecipitate membrane proteins from the solubilized P2 fraction of mouse PAG has been described in detail (Garzón et al, 2005b). Briefly, for nondenaturing conditions about 1 mg protein from PAG membranes was sonicated in 50 mM Tris HCl (pH 7.7), 50 mM NaCl, 1% Nonidet P-40, in the presence of protease and phosphatase inhibitors, and H89.…”
Section: Pull-down Assaysmentioning
confidence: 99%
“…RGS9-2 is particularly highly enriched in striatum and, although expressed at substantially lower levels in PAG and spinal cord, is present [45]. In vitro experiments performed with mouse PAG membranes showed that mu opioid receptor could be co-immunoprecipitated with α-subunits of G i/o/z/q/11 proteins, Gβ 1/2 subunits as well as both RGS9-2 and its partner protein Gβ 5 [46]. These interactions were modulated by morphine since 30 minutes and 3 hours after drug administration the coimmunoprecipitation of mu receptor-Gα subunit was reduced up to 50% whilst the interaction Gα-RGS9-2 was conversely increased.…”
Section: Regulators Of G-protein Signalling (Rgs) Is Other Family Of mentioning
confidence: 99%
“…The signaling pathways involved in the recruitment of PKC␥ to RGS proteins and MOR have been intensively studied , 2011. The physical interaction with activated PKC may easily phosphorylate RGS proteins and increase their binding to 14-3-3 proteins (Garzó n et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms documented for uncoupling is the formation of a G␣, RGS9-2, and 14-3-3 proteins complex (Garzó n et al, 2005). The formation of this complex is accompanied by serine phosphorylation of RGS9-2.…”
Section: Morphine-induced Translocation Of Pkc Was Attenuated In Nox1mentioning
confidence: 99%